Numerical study of a fish swimming in hydrokinetic turbine wake - Marianela Machuca Macias; Rafael Castilho Faria Mendes; José Hermenegildo Garcia-Ortiz; Taygoara Felamingo Oliveira; Antonio C.P. Brasil Junior (Journal of Ocean Engineering and Science)
The environmental effects of hydrokinetic turbines are still under investigation, reflecting the emerging status of this technology. This study investigates the interaction between hydrokinetic rotor wakes and fish swimming, revealing insights into fish biomechanics in complex flows and assessing the environmental implications of marine energy solutions. We conducted numerical simulations with the URANS approach and k−ω−SST turbulence closure model to predict three-dimensional turbulent flow in the OpenFOAM software. The hydrokinetic rotor wake was simulated employing the actuator line method, providing a computationally efficient alternative to full geometry simulations. For accurate replication of the motion of a fish-like tuna (Thunnus atlanticus), dynamic adaptive mesh discretization was employed. The results offer a comparative analysis of fish swimming performance within the wake rotor, particularly when immersed in the tip blade vortex, contrasted with scenarios where fish swim in undisturbed flow conditions. The analysis encompasses three-dimensional wake structures, force generation, efficiency, and equilibrium states (balancing drag and thrust) across varying Swimming numbers (Sw). Key findings include the enhanced attachment of the leading-edge vortex due to the caudal fin’s interaction with the tip blade vortex, resulting in improved auto-propulsive force production; a reduced tail stride frequency observed in fish swimming downstream of the rotor to achieve longitudinal force balance compared to unperturbed flow; and transverse hydrodynamic forces pushing fish radially away from the wake’s influence zone, potentially mitigating the risk of collision with turbine blades.